Protective Effect of Self-Compassion to Emotional Response among Students with Chronic Academic Stress - Zhang, Yonghong; Luo, Xi; Che, Xianwei; Duan, Wenjie (Frontiers in Psychology, 2016)
The literature has shown that self-compassion is a protective factor of an individual’s emo-tional response to chronic stress. However, this stress-buffering effect has not been complete-ly analyzed in individuals who report significantly high academic stress. The present study explored the role of self-compassion in a group of undergraduate students who experience chronic academic stress. A total of 208 undergraduate students who were preparing for the Postgraduate Entrance Examination (PEE) were recruited and completed the Self-Compassion Scale, Adolescent Self-Rating Life Event Check List, and Positive and Negative Affect Schedule. Differences analysis confirmed that the participants reported significantly higher academic stress than their peers who were not preparing for PEE. Self-compassion positively related to positive affect but negatively related to negative affect and learning stress. Further analysis showed that self-compassion negatively mediated the relationship be-tween chronic academic stress and negative affect. Findings imply that self-compassion-centered interventions can be developed in the educational context to assist students cope with chronic academic stress.